Public stigma against family members of people with mental illness: findings from the Gilgel Gibe Field Research Center (GGFRC), Southwest Ethiopia - Eshetu Girma; Anne Maria Möller-Leimkühler; Norbert Müller; Sandra Dehning; Guenter Froeschl; Markos Tesfaye (2014)
Public stigma against family members of people with mental illness is a negative attitude by the public which blame family members for the mental illness of their relatives. Family stigma can result in self social restrictions, delay in treatment seeking and poor quality of life. This study aimed at investigating the degree and correlates of family stigma. A quantitative cross-sectional house to house survey was conducted among 845 randomly selected urban and rural community members in the Gilgel Gibe Field Research Center, Southwest Ethiopia. An interviewer administered and pre-tested questionnaire adapted from other studies was used to measure the degree of family stigma and to determine its correlates. Data entry was done by using EPI-DATA and the analysis was performed using STATA software. Unadjusted and adjusted linear regression analysis was done to identify the correlates of family stigma. Among the total 845 respondents, 81.18% were female. On a range of 1 to 5 score, the mean family stigma score was 2.16 (±0.49). In a multivariate analysis, rural residents had significantly higher stigma scores (std. β = 0.43, P < 0.001) than urban residents. As the number of perceived signs (std. β = -0.07, P < 0.05), perceived supernatural (std. β = -0.12, P < 0.01) and psychosocial and biological (std. β = -0.11, P < 0.01) explanations of mental illness increased, the stigma scores decreased significantly. High supernatural explanation of mental illness was significantly correlated with lower stigma among individuals with lower level of exposure to people with mental illness (PWMI). On the other hand, high exposure to PWMI was significantly associated with lower stigma among respondents who had high education. Stigma scores increased with increasing income among respondents who had lower educational status. Our findings revealed moderate level of family stigma. Place of residence, perceived signs and explanations of mental illness were independent correlates of public stigma against family members of people with mental illness. Therefore, mental health communication programs to inform explanations and signs of mental illness need to be implemented.